Is management of past and forecasted earnings by IPO firms associated with insider trading? - Chua, Jia Yin. (2008)
The objective of our paper is to investigate whether management of past or forecasted earnings by IPO firms in Singapore is associated with insider trading. We examine the reported earnings and forecasted earnings in IPO prospectuses and investigate the relationships between insider trading, earnings management, forecast issuance and forecast bias.